AJINING DHIRI SAKA OBAHING DRIJI - Mudjijono Mudjijono (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2017)
Referring to the social conditions seen via social media today, this study has two research questions: 1) Are control and supervision needed for school age children using mobile phones?; and 2) Who are the right persons who would control them and provide the supervision? Using Malinowsky's functional approach, this research draw the data from observation and interviews from two schools in Yogyakarta. The results of the study indicate that school age children should be controlled in using mobile phones and this would be the responsibility of parents, elder member in the family, and teachers.